Adherence to COPD free triple inhaled therapy in the real world: a primary care based study. (17th June 2020) - Zucchelli, Alberto; Vetrano, Davide L.; Bianchini, Elisa; Lombardo, Francesco Paolo; Piraino, Alessio; Zibellini, Marco; Ricci, Alberto; Marengoni, Alessandra; Lapi, Francesco; Cricelli, Claudio
Abstract: Introduction: The development of new pharmacological treatments for chronic obstructive pulmonary disease (COPD) has improved health‐related quality of life of patients. However, suboptimal adherence may limit its potential. Objective: The aim of the present study was to assess the adherence to free triple inhaled therapy and to investigate poor adherence determinants among primary care patients. Methods: Data were derived from a primary care database in Italy. Patients aged 40+ affected by COPD and prescribed with inhaled corticosteroids, long‐acting beta agonists and long‐acting muscarinic antagonists (N = 3177) were enrolled. Low adherence was defined as a proportion of days covered (PDC) by medications prescription lower than 80%. Predictors of low adherence were tested using logistic regression models. Results and conclusions: The 85% of enrolled patients showed poor adherence to free triple inhaled therapy. Comorbidities, such as heart failure (OR 1.78, 95%CI 1.19‐2.75), depression (OR 1.41, 95%CI 1.06‐1.88) and peripheral vascular disease (OR 1.32, 95%CI 1.01‐1.74) were associated with poor adherence. Former (OR 0.52, 95%CI 0.34‐0.78) or current smokers (OR 0.61, 95%CI 0.41‐0.93) and patients with more severe airways obstruction or history of severe exacerbations (OR 0.64, 95%CI 0.52‐0.79) were less likely to exhibit poor adherence. Real‐world adherence to triple inhaled therapy with different inhalers is generally low. Higher GOLD airways obstruction stage and current or former smoking status are associated with increased adherence to treatment. Reduced perceived benefit on symptoms control is probably linked to poorer adherence to free triple therapy.